Vaikų knygos leidyba Lietuvoje 1940-1955 metais - Mozūraitė, Vita (Knygotyra, 1992)
The State Publishing House of the Lithuanian SSR and some private publishing houses published children’s books during the period from June 1940 until June 1941. They published 49 children’s books in 277,500 copies. During the German occupation, children’s books were published in Moscow, where the State Publishing House operated, and some were published in Lithuania. After the end of the war in 1945, new publishing houses were established in Lithuania, and all of them published books for children. The majority of children’s books were published by the State Publishing House of Fiction Literature. During eleven years, 588 children’s books were published in 9,345,400 copies. Fiction books accounted for 85.9% of that number. Censorship, a shortage of translators and editors, and difficulties with publishing hindered the production of children’s books. Initially, their prices were very high, but from 1949 onwards, they began to decrease. Often, publication was delayed due to a shortage of illustrators for children’s books or due to unsatisfactory work by illustrators. A Section of Children’s Literature and a Commission of Illustrators were created in the Union of Writers and at the State Publishing House of Fiction Literature to improve the publication of children’s books. The average number of children’s books published increased 2.5 times from 1945 to 1955.